2014
DOI: 10.4102/ac.v14i1.220
|View full text |Cite
|
Sign up to set email alerts
|

First-time versus repeat visitors at the Kruger National Park

Abstract: Purpose: The aim of this research is to segment visitors at the Kruger National Park based on the frequency of visitation in order to distinguish between first-time and repeat park visitors. Problem investigated:The Kruger National Park (KNP) in South Africa is one of the world's most renowned wildlife reserves. The KNP is in great demand because it is regarded as an all-inclusive holiday destination that provides tourists with a unique nature and leisure experience. As a result, the park attracts over one mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 39 publications
5
38
1
1
Order By: Relevance
“…Most of the respondents took a spontaneous decision to visit SNR which implies that they did not plan long in advance for their trip. These findings differ considerably from findings of earlier studies by Saayman and Slabbert (2004), Van der Merwe and Saayman (2008), and Kruger et al (2014) who found that visitors to http://www.sajbm.org…”
Section: Respondent Profilecontrasting
confidence: 57%
See 4 more Smart Citations
“…Most of the respondents took a spontaneous decision to visit SNR which implies that they did not plan long in advance for their trip. These findings differ considerably from findings of earlier studies by Saayman and Slabbert (2004), Van der Merwe and Saayman (2008), and Kruger et al (2014) who found that visitors to http://www.sajbm.org…”
Section: Respondent Profilecontrasting
confidence: 57%
“…These previous studies by Beh and Bruyere (2007), Kruger and Saayman (2013), Hermann and Du Plessis (2014) and Kruger et al (2014) were proved reliable and thus deemed suitable…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations